The Piesberg: A NW-German site of international importance for the Pennsylvanian (Late Carboniferous) - Angelika Leipner; Tobias Fischer; Patrick Chellouche (Geoconservation Research)
Piesberg quarry is famous for its Upper Carboniferous plant and arthropod fossils, including several holotypes of flying insects. The high degree of maturity of the Piesberg strata, such as the presence of anthracitic coal, quartzite, and large quartz crystals, led to controversies over a possible underlying thermal anomaly. The Piesberg is of further importance for correlation between the deep underground of northwestern Germany and the Ruhr basin coal field, as well as the Pennsylvanian coal areas in North America, and for investigations of Upper Carboniferous tight gas fields. The importance of the Piesberg for international geosciences has been enabled through its very rich mining history beginning in the Middle Ages and its long scientific history beginning at the end of the 18th century. Today, the Piesberg is not only one of the largest active quarry sites in Europe, but also a local recreation and hiking area. While the Museum am Schölerberg in Osnabrück protects its paleontological heritage through ongoing excavations and houses the world’s largest fossil and mineral collection from Piesberg, the UNESCO Global Geopark TERRA.vita and the city of Osnabrück conserve its geological heritage and promote environmental education through the Piesberg Cultural and Environmental Park. This paper highlights the international importance of the Piesberg by compiling its fossil record and paleoenvironmental interpretations. We also present preliminary data on new floral and faunal elements found in a recently discovered lake deposit. Further, the very rich mining history is briefly outlined and geoconservation and geotouristic measures are described.